Redox regulation of p53, redox effectors regulated by p53: A subtle balance - Maillet, A.; Pervaiz, Shazib (Mary Ann Liebert, Inc. Publishers, 2012)
Significance: Reactive oxygen species (ROS), generated by cells as side products of biological reactions, function as secondary messengers by impacting a host of cellular networks involved in maintaining normal homeostatic growth as well as pathological disease states. Redox-sensitive proteins, such as the tumor suppressor protein p53, are susceptible to ROS-dependent modifications, which could impact their activities and/or biological functions. Recent Advances: p53 is a transcription factor that controls a wide variety of target genes and regulates numerous cellular functions in response to stresses that lead to genomic instability. Thus, redox modifications of p53 could impact cell fate signaling and could have profound effects on pathways fundamental to maintaining cell and tissue integrity. Critical Issues: Recent studies present evidence that ROS function upstream of p53 in some model systems, while in others ROS production could be a downstream effect of p53 activation. Future Directions: In this review, we describe how ROS production regulates p53 activity and how p53 can, in turn, influence cellular ROS production. © 2012 Mary Ann Liebert, Inc.